506 The tumor immune microenvironment of metastatic osteosarcoma is marked by lymphocyte exclusion and impacts patient progression-free survival. (10th December 2020) - Ligon, John; Choi, Woonyoung; Cojocaru, Gady; Fu, Wei; Hsiue, Emily; Oke, Teniola; Morris, Carol; Levin, Adam; Rhee, Daniel; McConkey, David; Anders, Robert; Pardoll, Drew; et al.
Abstract : Background: Patients with relapsed metastatic osteosarcoma have no effective treatments available to them, 1 and immunotherapy thus far has not succeeded in improving outcomes. 2–5 We aim to understand the immune architecture of the tumor microenvironment (TME) of osteosarcoma, with the goal of harnessing the immune system as a major therapeutic strategy for the treatment of patients with osteosarcoma. Methods: 66 osteosarcoma tissue specimens were stained and analyzed by immunohistochemistry. Tumor-infiltrating lymphocytes (TILs) from 25 specimens were profiled by functional multiparameter flow cytometry (MFC). Distinct regions from 16 pulmonary metastases (PMs) were microdissected, and RNA was extracted to perform comparative transcriptomic studies. Clinical follow-up (median 24 months) was available from resection. Results: Digital image analysis of immunohistochemistry demonstrated significantly higher infiltrating immune cells in the PMs compared to primary bone tumors, concentrated at the tumor-normal lung 'PM interface' region, and elevated expression of multiple immune checkpoint molecules at the PM interface (figure 1 ). MFC confirmed the increased expression of the immune checkpoint molecules programmed cell death 1 (PD-1, p<0.01) and lymphocyte activation gene 3 (LAG-3, p<0.01), as well as the activation marker IFN-γ (p<0.05) in CD8+ TILs. Gene expression profiling provided further evidence for the presence of TILs with expression of activation markers and inhibitory immune checkpoint molecules at the PM interface compared to the PM interior (figure 2 ). A strong M2 macrophage signature was present in both regions. Further analysis revealed that genes related to neutrophil and myeloid cell chemotaxis and known to be associated with polymorphonuclear myeloid-derived suppressor cells were highly expressed at the PM interface, along with genes for multiple subsets of dendritic cells (figure 3 ). Expression of PD-L1, LAG-3, and CSF1R at the PM interface were associated with worse progression-free survival (PFS), while gene sets associated with productive T cell immune response were associated with improved PFS (figure 4 ). Conclusions: In contrast to primary bone osteosarcoma 'immune deserts, ' osteosarcoma PMs represent an 'immune-excluded' TME where immune cells are present but are halted at the PM interface. TILs can produce effector cytokines, suggesting their capability of activation and recognition of tumor antigens. Our findings suggest cooperative immunosuppressive mechanisms in osteosarcoma PMs that prevent TILs from penetrating into the PM interior, including immune checkpoint molecule expression and the presence of immunosuppressive myeloid cells. We identify cellular and molecular signatures that are associated with PFS of patients, which could be potentially manipulated for successful immunotherapy. Ethics Approval: This study was approved by Johns Hopkins University's Ethics Board, approval number FWA00005752. References: Mirabello L, Troisi RJ, Savage SA. Osteosarcoma incidence and survival rates from 1973 to 2004: Data from the surveillance, epidemiology, and end results program. Cancer 2009;115(7):1531–43. Tawbi HA, Burgess M, Bolejack V, Van Tine BA, Schuetze SM, Hu J, et al. Pembrolizumab in advanced soft-tissue sarcoma and bone sarcoma (SARC028): A multicentre, two-cohort, single-arm, open-label, phase 2 trial. Lancet Oncol 2017;18(11):1493–501. Davis KL, Fox E, Merchant MS, Reid JM, Kudgus RA, Liu X, et al. Nivolumab in children and young adults with relapsed or refractory solid tumours or lymphoma (ADVL1412): A multicentre, open-label, single-arm, phase 1–2 trial. Lancet Oncol 2020;21(4):541–50. D'Angelo SP, Mahoney MR, Van Tine BA, Atkins J, Milhem MM, Jahagirdar BN, et al. Nivolumab with or without ipilimumab treatment for metastatic sarcoma (alliance A091401): Two open-label, non-comparative, randomised, phase 2 trials. Lancet Oncol 2018;19(3):416–26. Paoluzzi L, Cacavio A, Ghesani M, Karambelkar A, Rapkiewicz A, Weber J, et al. Response to anti-PD1 therapy with nivolumab in metastatic sarcomas. Clin Sarcoma Res 2016;6 :24.